Understanding couple migration towards core and peripheral regions: The role of men's and women's education - Niels Kooiman; Marjolijn Das (Comparative Population Studies (CPoS), 2022)
Numerous studies have demonstrated that men's educational profiles dominate couple migration decisions. However, most of these investigated the US context or were conducted in the previous century. This study examines the role of both partners' educational attainments in couple migration in recent years in a new context: the Netherlands. The Netherlands is one of the countries in which women surpass men in educational attainment. We take a geographical perspective and test Costa and Kahn's (2000) hypothesis that power couples - two partners with university degrees - are more likely than other couples to migrate to metropolitan areas with dense labour markets in order to solve their "colocation problem." Data are derived from the Dutch Labour Force Survey between 2006 and 2015. The research population consists of all opposite-sex married and unmarried couples aged 18-45 (N=90,314 couples). By linking the respondents to integral register data, we tracked all couples until three years after the interview date. The results show that both men's and women's human capital increases migration propensities, although effect sizes are relatively small. Social factors such as the geographical distance to birthplace and parents appear to play a significant role in couple migration. We found only partial support for Costa and Kahn's (2000) colocation hypothesis. Power couples who live in the core region are less likely than other couples to migrate to more peripherally located regions. However, periphery-to-core migration is only affected by the male partner's human capital, not by hers. Hence, the concentration of power couples in Dutch metropolitan areas probably stems from highly educated, single, young, urban adults who migrated there individually and who tend to stay there after union formation.
urn:nbn:de:bib-cpos-2022-12en4
Keywords: 300; Internal migration; Family migration; Human capital; Core and peripheral regions; Gender (in)equality